Sulfur Fertilization Influence on Growth and Yield Traits of Three Korean Soybean Varieties - Md. Alamgir Kabir; Wook Kim; Hong Wei Wang; Qin Yao; Hyeok Kwon; Thirupathi Karuppanapandian (Hasanuddin University, 2016)
Field experiment was carried out at the Research Farm of Korea University, Republic of Korea to study effects of sulfur (S) fertilization on growth traits, yield and yield components of three Korean soybean varieties (Poongsunnamulkong, Saedanbaekkong and Daewonkong). Seeds were sown on black polythene mulched soil bed at the spacing of 15 X 60 cm both at control and sulfur fertilized (gypsum with 16% sulfur content at the rate of 200kg ha-1) plots following a Randomized Complete Block Design of the experiment applying three doses of sulfur together at the time of seed sowing and two doses together at V4 vegetative growth stage (4 nodes on the main stem beginning with the unifoliate node). The results showed that sulfur fertilization significantly increased all studied growth traits of three Soybean varieties except plant height when they all reached physiological maturity stage (120 DAS). It was also evident that sulfur fertilization in the form of gypsum can also increase the number and weight of soybean root nodules and enhance the ability of nitrogen fixation, and so reduce the input of nitrogen fertilizer. Similarly, all the studied yield and yield component related parameters were also significantly influenced by sulfur fertilization except seed number per pod and 100 seed weight. Varieties and sulfur fertilization also interacted significantly in all studied growth traits but the notable sole interaction effect was in plant height. Leaf area of Poongsunnamulkong and Saedanbaekkong variety increased significantly with sulfur fertilization while it was decreased significantly for Daewonkong. Similar trend was observed in their production of number of pods per plant and grain yield per plant indicating leaf area increment by sulfur fertilization played an important role in increasing yield of Poongsunnamulkong and Saedanbaekkong varieties though their performance was reverse in other growth traits. The improvement in growth and yield attributes after sulfur fertilization led to higher biological yield and enhanced seed yield.